(untitled) (Analele Universității București. Limba și literatură română, 2024)
On July 12th 2023, Elon Musk announced the creation of the xAi corporation, the aim of which is, according to the program put forth by its author, “understanding the true nature of the Universe”. 507 years after the publication of Thomas Morus’ Utopia, the trailblazing text of a concept which has moulded the post-Medieval European imaginary, the questions related to the morphology of the territories which we occupy or which we invent for ourselves are being reformulated. The present essay sets out to analyse several elements of a technoscientific flow of ideas which, throughout half a millennium, have been competing, beyond the cover of fiction, against the model of Christian monotheism.